SRPK2 Expression and Beta-Amyloid Accumulation Are Associated With BV2 Microglia Activation - Tian, Ziqi; Zeng, Wenfang; Yan, Cuihuan; Li, Qiang; Li, Nan; Ruan, Lin; Li, Jie; Yao, Xiaoguang; Li, Si (Frontiers in Integrative Neuroscience, 2022)
Introduction The extracellular deposition of β-amyloid (Aβ) is a pathological hallmark in Alzheimer's disease (AD), which induces microglial activation in the pathology of AD. The expression of serine/threonine-protein kinase 2 (SRPK2) is increased in the brain tissues of patients with AD. In this study, we examined the effect of SRPK2 in the activation of microglia. Methods Microglia (BV2) cells were cultured and the expression of SRPK2 was enhanced by transfection of SRPK2 recombinant vectors or knockdown by SRPK2 small interfering RNA (siRNA). The cells were stimulated by lipopolysaccharide (LPS) + interferon-γ (IFN-γ) or Aβ in vitro, generating inflammatory cytokines [tumor necrosis factor-α (TNF-α), interleukin (IL)-10, and IL-6], which were investigated by real-time quantitative PCR (qPCR) and ELISA. The proliferation ability of the BV2 cells with/without SRPK2 expression was evaluated by WST-1 under pressure in the presence of Aβ. The effects of SRPK2 on microglia polarization were evaluated by investigating the expression of CD16/32 and CD206 by western blot and the expression of ionized calcium-binding adapter molecule-1 (IBA-1) and arginase-1 (Arg-1) by immunofluorescence. Hippocampal cells HT-22 were cultured with a BV2 cell (with/without SRPK2 expression)-derived medium stimulated by Aβ or LPS + IFN-γ, prior to the evaluation of HT-22 cytotoxicity by assessment of cell viability. Possible relationships between Akt and SRPK2 in the BV2 cells were investigated by western blot. Results The expression of SRPK2 was related to the phenotype polarization changes of microglia with increased expression of CD16/32 and IBA-1. The expression of proinflammatory cytokines IL-6 and TNF-α was increased, whereas the expression of anti-inflammatory cytokine IL-10 was decreased in the BV2 cells with SRPK2 overexpression. Moreover, with the expression enhancement of SRPK2, the BV2 cells had a higher proliferation rate. Aβ treatment can promote SRPK2 expression in BV2 cells. Aβ or LPS + IFN-γ promoted the production of cytokines IL-6 and TNF-α but decreased cytokine IL-10 in the BV2 cells. SRPK2 deficiency alleviated the cytotoxic effects of Aβ or LPS + IFN-γ exposed microglia on HT22 cells. In addition, the activated Akt pathway promoted the expression of SRPK2 in the BV2 cells. Conclusion Our data have found that enhanced SRPK2 expression contributed to the proinflammatory activation of microglia. Thus, SRPK2 may be a key modulating pathway of inflammatory mediators in AD pathology.